Olympia, Griechenland. Die Rekontextualisierung von Befunden und Funden der Schatzhausterrasse von Olympia – Ein Zwischenbericht. Die Arbeiten der Jahre 2019 und 2020 - Boecker, Velia; Zimmermann, Regina (e-Forschungsberichte des DAI, 2021)
The digital documentation system iDAI.field 2.0. provides the basis to evaluate excavation data and publish them online. »Die Schatzhausterrasse von Olympia: Rekontextualisierung von Befunden und Funden« is one of the projects, in which the retrospective processing and publication of earlier excavations is being tested. The treasuries at Olympia have been excavated in the early campaigns in Olympia between 1875–1881. The documentation consists of site notebooks, handwritten reports, sketches, registers as well as the publication of the excavation results and part of the finds. The project aims to combine these data sets and recontextualize them in iDAI.field 2.0 to publish the archaeological contexts and the related finds online.